Isolation, Identification and Production of Encapsulated Bradyrhizobium japonicum and Study on their Viability - Chhetri, Til Kumari; Subedee, Bijay Raj; Pant, Bijaya (Nepal Journal of Biotechnology, 2019)
Rhizobium, a nitrogen-fixing bacteria is the essential feature of leguminous plants which is essential for the regeneration of nutrient-deficient soil. This study was aimed to isolate, identify, mass culture and immobilize Bradyrhizoium japonicum in encapsulated form and test their viability. Root nodules were sterilized, grinded and cultured aseptically in YEMA media containing Congo red. The obtained colon was sub-cultured to get a pure culture and different biochemical tests were conducted which proved Bradyrhizobium japonicum as the slow-growing species. The test shows a positive result of catalase production and nodulation test whereas the pH tolerance test shows more tolerance to the acidic pH. Similarly, Bradyrhizaobium japonicum can tolerate 1% and 2% NaCl concentration and it doesn’t show resistance to the penicillin disc of 10mg. The mass culture and encapsulation with sodium alginate adding sucrose as nutrient proved the simplicity for handling. Altogether 548 beads were prepared from the 100ml of the cultured broths which were viable for more than 190 days at 1%, 2% and 3% sucrose concentration but less viable at 5% and 10% sucrose concentration under room temperature.